International Migration as State Policy: The Philippine Experience As Model and Myth - Tigno, Jorge V. (Kasarinlan: Philippine Journal of Third World Studies; Vol 6 No 1 (1990), 2008)
The present Philippine state has failed as an oracle of development. Altogether, this policy framework called labor export is certainly a very unsound development policy. A systematic attempt (i.e. to use migration as a social and historic phenomenon) to come with a labor export policy will necessarily reflect the intensifying state of the international division of labor as dictated by advanced capitalist countries to the detriment of the developing or underdeveloped ones. Migration policy as a modern-day talisman of sorts simply is not possible. In terms of welfare, investment and employment targets, labor export cannot possibly achieve genuine national development objectives or broad-based development. Decades of experience already attest to this. Migration policy as state policy rejects any notion of decentralization or distribution of wealth and social power. In the final analysis, the unfortunate prospect is that migration as a function of free market forces is but a myth just as migration as a vision for attaining national development is a false and dangerous panacea.